THE IMPACT OF CRITICAL THINKING ON LEARNERS’ EFL VOCABULARY RETENTION: THE ARAB CONTEXT - Tariq Elyas; Budor S. Al-Zahrani (Indonesian EFL Journal, 2019)
This experimental study aimed to investigate the impact of a critical thinking based pedagogical approach on learners’ retention ability of EFL vocabulary. There were two groups in the study: an experimental and a control group. The experimental group received vocabulary instruction with a critical thinking-based approach whereas the control group was taught in the conventional methods of vocabulary teaching. The treatment consisted of seven lessons delivered over 12 weeks. At the end of the treatment, the immediate posttest was administered and two weeks after the immediate posttest, the delayed posttest was administered. The resulting data were subjected to descriptive and inferential statistical analysis using SPSS software. The results showed that the experimental group outperformed the control group. Based on these results, the researchers concluded that the adopted critical thinking-oriented language instruction to EFL vocabulary has a positive effect on vocabulary retention, with implications for policy-makers, teacher trainers and teachers.